Outcomes in pulmonary sarcoidosis: results of a newly implemented prednisone protocol.: Results of newly implemented prednisone protocol. - Kampstra, Nynke; van der Wees , Philip J; van Beek, Frouke T.; Biesma, Douwe H.; Grutters, Jan C.; van der Nat, Paul B. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim Prednisone is used as first-line therapy for patients with pulmonary sarcoidosis. There is however no clear association between prednisone dose and FVC change in patients with pulmonary sarcoidosis. In order to improve our standard of care we introduced a more conservative prednisone protocol. Methods This study is a single centre observational study, applying value-based healthcare (VBHC) and quality improvement (QI) principles. Prednisone intake was reduced from a starting dose of 40 mg to a starting dose of 20 mg. Primary outcomes evaluated were FVC, FEV1 and DLCO % predicted. The secondary outcome measure was BMI. Results 369 patients were included in the old-cohort and 215 in the new-cohort. In the old-cohort, 182 (49.0%) of the patients were treated with prednisone. In total, 114 patients (62.6%) were treated according to the old protocol with a mean initial prednisone dose of 32.1 ±14.2 mg. In the new-cohort, 93 patients (45.0%) were treated with prednisone of which 53 patients (57.0%) received prednisone according to the new protocol. The mean initial prednisone dose in the new-cohort was 21.4 ±9.8 mg. Changes in FVC and FEV1 % predicted did not vary. Change in % predicted DLCO was 2.4 ±9.3 for the old-cohort and -1.3 ±11.4 for the new-cohort (p = 0.01). No statistically significant changes in BMI were observed. Conclusions Our results indicate that in more than half of the patients the new protocol was followed. Data support the observation that a more conservative prednisone regimen might be equally effective, looking at changes in pulmonary function and BMI.